2012
DOI: 10.1016/j.cca.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations of cholesteryl ester transfer protein (CETP) gene in Japanese hyperalphalipoproteinemic subjects

Abstract: Background: The half of hyperalphalipoproteinemia (HALP) in Japan is caused by CETP gene mutations. Other than two prevalent mutations (D442G and Intron 14 splicing donor site +1 G>A), some rare CETP mutations are found in Japanese HALP subjects.Methods: CETP gene analysis of genomic DNA from subjects was performed by restriction fragment length polymorphism (RFLP) and sequencing analysis. Mutations which were suspected to cause a splicing defect or a protein secretion defect were investigated in COS-1 cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, it is likely to truncate the monomers, impairing the synthetase-binding domain. Similar variants leading to protein truncation have been reported previously [13, 19, 20]. Therefore, we believe that the variant c.773 + 4A > C is associated with the pathogenesis of CTLN1.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, it is likely to truncate the monomers, impairing the synthetase-binding domain. Similar variants leading to protein truncation have been reported previously [13, 19, 20]. Therefore, we believe that the variant c.773 + 4A > C is associated with the pathogenesis of CTLN1.…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately, the causes of the extremely high HDL-C in subjects in this study are unclear because gene sequencing and measurement of CETP activity were not conducted. However, it has been reported that in half of individuals with high HDL-C in Japan a CETP gene mutation is responsible [43].…”
Section: Discussionmentioning
confidence: 99%
“…p.Leu168 is not evolutionarily conserved (S4 Fig), but introducing a proline at this position could make the backbone less flexible and affect protein folding. Ohtani et al [23] have found that L278R is not secreted. p.Leu278 is highly conserved and contributes to the lining of the hydrophobic tunnel.…”
Section: Plos Onementioning
confidence: 99%